A review of brain regions and associated post-concussion symptoms - Danielli, Ethan; Simard, Nicholas; DeMatteo, Carol A.; Kumbhare, Dinesh; Ulmer, Stephan; Noseworthy, Michael D. (Frontiers in Neurology, 2023)
The human brain is an exceptionally complex organ that is comprised of billions of neurons. Therefore, when a traumatic event such as concussion occurs, somatic, cognitive, behavioral and sleep impairments are the common outcome. Each concussion is unique in the sense that the magnitude of biomechanical forces, and the direction, rotation, and source of those forces, is different for each concussive event. This helps to explain the unpredictable nature of post-concussion symptoms that can arise and resolve. The purpose of this narrative review is to connect the